(untitled) (London Journal of Medical and Health Research, 2024)
Introduction: As healthcare sectors are complex, it’s difficult to handle the process involved in the management. The cost of healthcare is increasing so it is important to increase efficiency as well. Assessing appointment schedules and Turnaround time will help to analyze the workflow of the MRI department and optimize the processes. Methods: The methods used were cross-sectional, prospective, descriptive, quantitative analysis, and qualitative methods. The patients for the study were selected through random sampling techniques and in-person data gathering was performed. Results: Data was collected, and charted on an Excel tracker sheet, and in-depth analysis was performed. The tracker sheet included various study parameters like Registration Time, Waiting before changing, Changing Time, Waiting before Case history, Case History, Waiting before the scan, and MRI Scan Time. The data analysis included the average turnaround time for MRI i.e. from registration to scan was 1 hour 14 minutes. Discussion: The reasons that were causing the delay in the MRI department were enumerated. Reasons like carrying any metal object in the department, first preference for emergency patients, nature of the examination, and movement of the patient during the scan were studied in depth. Application: This study provides the pattern that was supposed to be followed for scheduling patient’s appointments in the MRI department and to optimize the turnaround time for the patient. The possible reasons causing a delay in the process of the MRI department by observing the current practices in the MRI department including the infrastructure, and staffing.